Performance Appraisal Design In The Grand Mutiara Hotel Housekeeping Division Using BARS Assessment Model - Muhammad Fachrurrozi Akbar; Christanto Triwibisono; Fida Nirmala Nugraha (International Journal of Innovation in Enterprise System, 2021)
Frequently receiving customers complaints makes the Grand Mutiara Hotel decrease in monthlyguests number, caused by customer’s dissatisfaction with the hotel’s facilities and services. It occursdue to the crew’s disappointment, especially in the housekeeping division dealing with theirworking-performance assessment to be an indicator of salary payment. Redesigning the assessmentwas carried out by paying attention to factors affecting the working performances. The subject ofthis research was the Grand Mutiara Hotel. This research utilized the BARS (Behavior AnchorRating Scale) method that was an effort to diagnose and reveal individual behavior to be suitablewith the company’s objectives. This method aimed to determine which factors influencing theworking-performance and delivering the assessing guideline containing clear indicators should be inthose factors. Sampling used a purposive random sampling by taking two respondents in each subgroup consisting of housekeeping, security, F&B, engineering, and front office divisions. Further,other samples were coming from supervisors of each sub-group, managers, and HRD. This studyindicates five factors affecting the working-performance, such as tangibility, reliability, assurance,responsiveness, and empathy.